To solve the equation \(x^2 + 2x = 3\) using a function graph, we first rearrange the equation into the standard form:
\[ x^2 + 2x - 3 = 0 \]
Now we can define a function \(f(x)\):
\[ f(x) = x^2 + 2x - 3 \]
Next, we will find the roots of the function \(f(x)\) where \(f(x) = 0\).
We can start by identifying the graph of the quadratic function \(f(x)\). The graph of a quadratic function is a parabola, and we can find the x-intercepts (the solutions to the equation) by either using factoring, completing the square, or the quadratic formula.
-
Factoring:
We want to factor the quadratic expression \(x^2 + 2x - 3\) into the form \((x + p)(x + q) = 0\).
Looking for two numbers that multiply to \(-3\) and add up to \(2\), we find:
\((x + 3)(x - 1) = 0\)
Setting each factor to zero gives:
\[ x + 3 = 0 \implies x = -3 \] \[ x - 1 = 0 \implies x = 1 \]
So the solutions to the equation \(x^2 + 2x = 3\) (or \(x^2 + 2x - 3 = 0\)) are:
\[ x = -3, \quad x = 1 \]
Now refer to the options provided:
- x=0,1
- x=2,0
- x=−3,1
- no solution
The correct response is:
x = -3, 1